tRNA-modifying enzyme mutations induce codon-specific mistranslation and protein aggregation in yeast - Tavares, Joana F. (2021)
Protein synthesis rate and accuracy are tightly controlled by the cell and are essential for proteome homoeostasis (proteostasis); however, the full picture of how mRNA translational factors maintain protein synthesis accuracy and co-translational protein folding are far from being fully understood. To address this question, we evaluated the role of 70 yeast tRNA-modifying enzyme genes on protein aggregation and used mass spectrometry to identify the aggregated proteins. We show that modification of uridine at anticodon position 34 (U34) by the tRNA-modifying enzymes Elp1, Elp3, Sml3 and Trm9 is critical for proteostasis, the mitochondrial tRNA-modifying enzyme Slm3 plays a fundamental role in general proteostasis and that stress response proteins whose genes are enriched in codons decoded by tRNAs lacking mcm5U34, mcm5s2U34, ncm5U34, ncm5Um34, modifications are overrepresented in protein aggregates of the ELP1, SLM3 and TRM9 KO strains. Increased rates of amino acid misincorporation were also detected in these strains at protein sites that specifically mapped to the codons sites that are decoded by the hypomodified tRNAs, demonstrating that U34 tRNA modifications safeguard the proteome from translational errors, protein misfolding and proteotoxic stress.